2013
DOI: 10.1167/iovs.13-11657
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Corneoscleral Topography

Abstract: Age is the main factor influencing CSP; this should be taken into consideration in contact lens design, IOL selection, and in the optimization of surgical procedures. Ocular topography also varied with height, sex, ethnicity, and refractive error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
84
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 31 publications
10
84
5
Order By: Relevance
“…Previous studies have shown that changing the base curve of a soft lens does not generally have a significant effect on lens fit [16] and this is because the lens fit is influenced by peripheral corneal topography [19] and the corneoscleral anatomy [20]. Currently marketed daily disposable silicone-hydrogel contact lenses differ in shape profile and material composition and the lack of correlation in lens fit between the brands indicates these features affect the lens fit differently for individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that changing the base curve of a soft lens does not generally have a significant effect on lens fit [16] and this is because the lens fit is influenced by peripheral corneal topography [19] and the corneoscleral anatomy [20]. Currently marketed daily disposable silicone-hydrogel contact lenses differ in shape profile and material composition and the lack of correlation in lens fit between the brands indicates these features affect the lens fit differently for individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…New insights [4,5] show us that practitioners shouldn't expect the limbal area, or corneo-scleral junction, to necessarily have the concave shape that would be expected based on theoretical considerations expressed in older and even current textbook chapters. In addition to this, these studies also indicate that, for the average eye, the ocular surface beyond the cornea is nonrotationally symmetrical in nature.…”
Section: Lens Centrationmentioning
confidence: 99%
“…Also, measuring techniques, up to recently limited to central keratometry, have been upgraded: first to limbal-to-limbal corneal coverage topography instruments, and most recently to instruments that can measure the limbal area and even beyond that (such as optical coherence tomography [3][4][5] and eye surface profilometry [6,7]), thus helping us better understand the shape of the corneo-scleral junction and the anterior surface. Studies by Hall et al [8] have indicated that there is a direct relationship between corneo-scleral shape and soft lens fitting characteristics.…”
mentioning
confidence: 99%
“…There is a wide variation in corneal diameter within the population; mean corneal diameter has been estimated at 13.4 mm for a UK population but with a range of more than 2.5 mm. 1,2 However, the diameters of spherical soft contact lens brands usually fall within a narrow range (14.0-14.2 mm). Conventionally, soft lens diameter is measured at room temperature (20°C) during manufacture and labeled accordingly.…”
mentioning
confidence: 99%
“…It is helpful, therefore, for contact lens practitioners to know the true diameter at ET (34°C) so as to find a better match between the lens type and ocular topography. 2 It is also helpful to know this parameter when modeling the on-eye fit of known lens designs; computer modeling has proved useful in helping to understand the interaction of lens geometry and fit. 6 A previous study measured the thermal response of 13 hydrogel and silicone hydrogel lens types and found that all lens types reduced in diameter by clinically significant amounts ($0.08 mm) when raised to ET, with the largest mean changes in silicone hydrogel and hydrogel lenses being with Biofinity (D0.35 mm) and ACUVUE 2 (D0.28 mm), respectively.…”
mentioning
confidence: 99%